Behaviour of RC-Deep Beam by GFRP Rubberized Concrete - Jumaa, Omaima.; Noaman, Ahmed; Mahmoud, Akram (Iraqi Journal of Civil Engineering, 2023)
In this study, the structural behaviour of RC-deep beams of glass fibre-reinforced polymer (GFRP) rubberized concrete is investigated. Rubberized concrete is manufactured by replacing fine sand aggregate with rubber crumbs in volumetric replacement ratios. The main variables were the crumb rubber content (0%, 10%, and 20%) and the main reinforcement ratio. Tested Six samples of deep beams with different dimensions (b = 150, h = 300 mm, L= 1400 mm) were under a four-point load until failure. The parameters under investigation were the mechanical properties of mixtures, load-midspan deflection curves, toughness, and the load-strain relationship. The results indicate that the increased crumb rubber content led to a decrease in the mechanical properties of rubberized concrete mixtures. It was found that the behaviour of all samples of rubberized concrete affected the deflection load curve, the ultimate load, and the increase in deflection. The sample R2-10% Rub showed the highest toughness among the tested samples, with an increase of 301.6% compared to the reference.